La place de la traduction dans l’univers du théâtre : le surtitrage en exemple - Lynda Kazi-Tani (Multilinguales)
Throughout history, translation has been a constant source of discovery of others, their cultural heritage, their knowledge and their vision of the world. It allows us to immerse ourselves in distant and little-known worlds, such as literature, poetry or science, transcending the constraints of time or geography. Over the decades, translation has evolved, moving closer to new technologies to give rise to new specialities, such as audiovisual translation with, among other things, dubbing and subtitling. However, there is a largely under-studied and little-known field of research at the crossroads of translation, the performing arts and technology : surtitling. Our intention in this study is to shed light on this professional practice by exploring its many dimensions. To do this, our research approach will encompass an in-depth analysis of both the theoretical and practical aspects of surtitling. The aim is to highlight the importance of surtitling in the contemporary artistic and linguistic landscape, while helping to bridge the remaining gaps between translation, the performing arts and technology.